PELATIHAN PENYEDIAAN GIZI SEIMBANG UNTUK BALITA - Sarni Anggoro (Jurnal Pengabmas Masyarakat Sehat, 2022)
Toddler period is a period of "anxiety" because growth is not as fast as the previous period or infancy. Nutritional problems that are often experienced by toddlers are Less Protein Energy, obesity (overweight), lack of vitamin A, Iodine Deficiency Disorders (IDD), iron deficiency anemia. Handling of nutritional problems must be handled individually according to the case suffered. Health and balanced nutritional intake according to their needs are the best prevention activities to overcome the emergence of nutritional problems. Community service activities are carried out by training on the provision of balanced food for toddlers in Bogem Hamlet, Caturharjo Village, Pandak, Bantul. The objective of this activity is to increase the knowledge and skills of mothers with children under five regarding the provision of balanced nutrition for their children. The target of the activity is mothers who have toddlers in Bogem Hamlet, Caturharjo Village, Pandak, Bantul. After finishing, the participants learned about balanced nutrition for toddlers and how to prepare it so that in the future children can become healthier.